Tuberculosis and associated factors among type 2 diabetic patients in Perak: a case control study - Kui, Choon Yong; Noor Azimah Muhammad,; Lim, Wei-Yin; Amar-Singh HSS, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This is a case-control study conducted with diabetic patients in Kinta, Kampar and Larut-Matang-Selama districts of Perak, Malaysia. We intended to determine the factors contributing to the development of active tuberculosis among diabetes patients. Cases were culture-proven and registered in the Malaysian National Tuberculosis Surveillance Registry (MyTB) from 2012 to 2018. Controls were diabetes patients identified from the National Diabetes Registry and were matched with cases based on the clinic in which they were registered at a ratio of 1:1. 119 cases and 119 controls were included in this study. Multivariate analysis was used to identify clinical factors associated with tuberculosis. Patient had increased odds of having tuberculosis if they had higher glycaemic (HbA1c) levels (OR=1.41, 95% CI 0.22-0.96, p<0.001) or nephropathy (OR=8.91, 95% CI 2.31-34.05, p<0.001). The odds ratio was lower if they have diabetes for at or more than 5 years (OR=0.46, 95% CI 0.22-0.96, p=0.04) and older (OR=0.96, CI 0.92-0.99, p=0.02). In conclusion, this study suggests that routine screening for tuberculosis in patients with diabetes should consider the diabetic duration, glycemic control, presence of nephropathy, and age of the patient.